L’ombra di Bruno: l’uomo tra finito e infinito. Incontro con Michele Ciliberto - Vari, Autori (Il sogno della farfalla, 2019)
The meeting, organized by the Cultural Association Amore and Psiche on 14.12.2007, followed the publication of Michele Ciliberto’s book, Giordano Bruno e il teatro della vita (Giordano Bruno and the theatre of life), in which the author identifies a strict connection between Bruno’s life and his thinking. When answering questions Ciliberto describes the Renaissance as a profoundly dramatic era, characterized by the dialectic between disenchantment and furore, in the midst of which the human and intellectual events of Bruno’s life distinguish themselves, among other things, for the original radicality of his criticism towards Christianity, for the importance he gives to the body-mind relationship, and for the peculiar declination towards the theme of images. The latter, intended not only as a reproduction of an external figure, but also as internal images, are linked to the theme of memory, central to Bruno, able to, beyond its instrumental aspect, capture an element of the process which allows man to measure himself with truth and with the infinite.